2020
DOI: 10.1521/pedi.2020.34.supp.42
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Emotional Responses and Therapeutic Alliance When Treating Adolescent Patients With Narcissistic Personality Disorder Subtypes: A Clinically Meaningful Empirical Investigation

Abstract: This study examined clinician emotional responses and therapeutic alliance in psychotherapy with adolescent patients with specific subtypes of narcissistic personality disorder (NPD). A national sample of therapists (N = 58) completed the Therapist Response Questionnaire for Adolescents to identify patterns of clinician response, the Working Alliance Inventory to evaluate the quality of alliance, and the Shedler-Westen Assessment Procedure-II for Adolescents to assess the personality pathology of a patient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…It should be also considered that both grandiose and vulnerable narcissistic traits can be present within the same person [ 6 , 68 ]. Research in adolescents has shown that NPD can be distinguished in three subtypes: predominantly grandiose/malignant, fragile and high-functioning/exhibitionistic [ 95 , 103 ]. However, feelings of grandiosity and vulnerability may still fluctuate on a state basis within the individual [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be also considered that both grandiose and vulnerable narcissistic traits can be present within the same person [ 6 , 68 ]. Research in adolescents has shown that NPD can be distinguished in three subtypes: predominantly grandiose/malignant, fragile and high-functioning/exhibitionistic [ 95 , 103 ]. However, feelings of grandiosity and vulnerability may still fluctuate on a state basis within the individual [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fostering self-compassion in treatment, including with young people, may counter the disruptive effects of shame by allowing one’s needs and sense of self, including negative aspects of the self, to be experienced [ 26 , 109 ]. The challenge here is that feelings of shame may relate to less self-compassion or even fear thereof in adolescents with narcissistic traits [ 110 , 111 ] and that therapists may show less warm responses to adolescents presenting with pathological narcissistic traits [ 103 ]. In clinical practice, it is important to be aware of emotional reactions to clients with narcissistic traits to be able to foster self-compassion [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea that grandiose individuals may have trouble expressing deeper emotional experience may also inform research around the negative effect grandiosity is thought to have on the therapeutic alliance (e.g., Zalman et al, 2019;Tanzilli and Gualco, 2020). Clients who are more grandiose in presentation may be less inclined to share their distress or divulge a need for help, placing strain on the alliance and leading to ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable pathological narcissism tends to involve interpersonal problems associated with being too cold, avoidant and exploitable, in contrast to the grandiose presentation, which is characterized by problems with being too vindictive, domineering, intrusive and over-nurturant (Pincus et al, 2009). The clinical utility of differentiating these two dimensions has been well argued (Cain et al, 2008), with grandiosity linked to lower treatment utilization, poor therapeutic alliance, and therapist responses characterized by anger and hopelessness (Pincus et al, 2014;Ronningstam, 2017;Tanzilli and Gualco, 2020).…”
Section: Introductionmentioning
confidence: 99%